Composting municipal biosolids in polyethylene sleeves with forced aeration: Process control, air emissions, sanitary and agronomic aspects. (September 2017) - Avidov, R.; Saadi, I.; Krassnovsky, A.; Hanan, A.; Medina, Sh.; Raviv, M.; Chen, Y.; Laor, Y.
Graphical abstract: Highlights: Municipal biosolids were composted in polyethylene sleeves for agricultural use. Thermophilic and aerobic conditions were controlled successfully. Odor control was primarily needed during the first three weeks of composting only. Salmonella, E. coli and coliforms were effectively reduced but regrowth might occur. The final product was found to be non-phytotoxic and beneficial as a soil additive. Abstract: Composting in polyethylene sleeves with forced aeration may minimize odor emissions, vectors attraction and leachates associated with open windrows. A disadvantage of this technology is the lack of mixing during composting, potentially leading to non-uniform products. In two pilot experiments using biosolids and green waste (1:1; v:v), thermophilic conditions (>45 °C) were maintained for two months, with successful control of oxygen levels and sufficient moisture. Emitted odors declined from 1.5–3.8 × 10 5 to 5.9 × 10 3 –2.3 × 10 4 odor units m −3 -air in the first 3 weeks of the process, emphasizing the need of odor control primarily during this period. Therefore, composting might be managed in two phases: (i) a closed sleeve for 6–8 weeks during which the odor is treated; (ii) an open pile (odor control is not necessary). Reduction of salmonella, E. coli and coliforms was effective initially, meeting the standards of "Class A" biosolids; however, total and fecal coliforms density increased after opening the second sleeve and exceeded the standard of 1000 most probable number (MPN) per g dry matter. Compost maturity was achieved in the open piles following the two sleeves and the final compost was non-phytotoxic and beneficial as a soil additive.